Effect of asymmetric solubility of diketopyrrolopyrrole-based polymers and PC71BMs in a binary solvent system on the performance of bulk heterojunction solar cells - Son, Seon Kyoung; Lee, Hyo-Sang; Ha, Jae Seung; Kim, Kyung Hwan; Son, Hae Jung; Ko, Min Jae; Kim, Honggon; Lee, Doh-Kwon; Kim, Jin Young; Lee, Wonmok; Park, Sungnam; Choi, Dong Hoon; et al. (ELSEVIER, 2014)
In this study, we demonstrated the effective morphological control of polymer:fullerene blends using three separate solvent systems: chloroform (CF), CF:1,8-diiodooctane (DIO), and CF:o-dichlorobenzene (ODCB). The polymer:fullerene blends are composed of two diketopyrrolopyrrole (DPP)-based polymers of P(DPP-alt-QT) and P(DPP-alt-DTBSe) and a fullerene derivative of [6,6]-phenyl-C71-butyric acid methyl ester (PC71BM), i.e., P(DPP-alt-QT):PC71BM or P(DPP-alt-DTBSe):PCTIBM. The CF:ODCB binary solvent exhibited the best photovoltaic performance among the three solvent systems for both polymer-based devices, although the CF:DIO also exhibited an improved performance compared to the CF system. By examining film morphology of the blend films, we found that the CF:ODCB enabled the most optimal nanoscale phase separation and the morphological features were strongly affected by the solubility of each material in the high boiling-point (BP) solvent. Specifically, the polymers have limited but slightly higher solubility in ODCB than in DIO, while the PC71BM molecules have a high solubility in both DIO and ODCB. Therefore, this work highlights that the optimally asymmetric solubility of each photoactive component in the high BP solvent is a critical factor to form the nanoscale, bicontinuous domains in the blend films and thereby to determine the performance of photovoltaic devices. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: CONJUGATED POLYMER; NANOSCALE MORPHOLOGY; PHOTOVOLTAIC CELLS; EFFICIENCY; DONOR; BAND; SELENOPHENE; MOBILITY; VOLTAGE; OXIDE